Unveiling the Veil of Mortality: Investigating the Multifaceted Causes and Consequences of Sudden Deaths through Post-Mortem Perspectives in Erbil City - Dilman Azad Hassan (Erbil Journal of Nursing and Midwifery)
Background and Objective: Percutaneous sudden death is still a great concern to humankind since it still affects a large population across the globe and has many causes and risk factors. This  paper looks at the various contributing factors to Sudden Deaths in Erbil, Iraq, focusing on examining gender differences and family predisposition.